ENDOPARASIT PADA USUS AYAM KAMPUNG (Gallus domesticus) - Devi Moenek; Aven B Oematan (JURNAL KAJIAN VETERINER, 2018)
The presence of parasites in the backyard chicken body can cause damage to certain organs. Endoparasites can inhibit growth and lead to decreased production of chicken. The aims of this study is to identify the type of endoparasitic worms that infect backyard chickens as well as calculate the presence of endoparasit levels in backyard chicken feces. Samples of backyard chicken were taken randomly as many as 35 animals from farms in Kelapa Lima sub-district, Kupang City and Kupang Tengah sub-district Kupang District. The samples were examined by native and sediment method. The results showed that the endoparasites found in the method chickens were Ascarida galli, Raillietina sp. and Oxyuris sp. eggs, With a presence frequency of 88,58%, 5,71 %, and 5,71% respectively.